Forage choice of the reintroduced black rhino and the availability of selected browse species at Majete Wildlife Reserve, Malawi - Krisztián Gyöngyi; Morten Elmeros (Pachyderm)
We investigated the forage choice of recently reintroduced black rhino and the availability of standing browse biomass in Majete Wildlife Reserve (MWR) in Malawi. Field work was conducted in the late hot–wet to early cool–dry season, a period that presented a broad botanical backdrop to collect forage data. Two management sub-areas of the eastern half of MWR constituted the larger study area. We recorded 59 diet species and 1,743 standard bite volumes along black rhino feeding trails with Mimosaceae and Fabaceae species dominating the diet. Out of the six main vegetation types, the Riverine and Alluvial matrix possessed the largest proportional standing browse biomass, with the widely distributed Low Altitude Mixed Woodland showing the greatest area-weighted scores. The High Altitude Miombo Woodland produced both the lowest average proportional and weighted browse availability for black rhino. By providing information on the selected diet species of black rhino and the availability of black rhino browse species in the reserve’s different vegetation types, this study provides the foundations for a better understanding of black rhino holding capacity of MWR. Results should help to identify potential release sites for future black rhino reintroduction schemes. A better understanding of the dietary attributes and feeding ecology of the Majete rhinos and the capacity of habitat to sustain their growing population will lead to better stock management (i.e. avoiding translocation stress when nearing holding capacity margins) and thus serve the long-term goals of augmenting the meta-population.